Freedom of Contract, Party Autonomy and Its Limit Under Cisg - Gül, İbrahim (My University, 2016)
CISG, sözleşmeye taraf olan devletlerde veya milletlerarası özel hukukun atıf yaptığı taraf devlette doğrudan uygulanır. Fakat CISG uluslararası satım sözleşmesine ilişkin her soruna, sözgelimi mülkiyet veya geçerlilik gibi sorunlara ilişkin bir hüküm içermez. Bu nedenle taraflar CISG'in kapsamadığı sorunlara uygulanacak ulusal hukuku seçmelidirler. Diğer yandan taraflar, CISG bağlamında bir nevi sözleşme özgürlüğü olarak adlandırılabilecek irade muhtariyetine sahiptir olduklarından CISG hükümlerini değiştirerek veya uyarlayarak sözleşme hükümlerini belirlemeyebilirler. CISG bağlamında irade muhtariyetine, ilke olarak sınırlama getirilmemiştir. CISG bağlamında irade muhtariyetine tek sınırlama, sözleşmeye taraf devlete uluslararası satım sözleşmesinin veya değişikliğinin yazılı şekilde yapılmasını zorunlu kılmak için çekince koyma hakkı veren CISG'nin 12. maddesidir

The CISG is directly applicable in Contracting States or when conflict of laws refers to the laws of Contracting States. However, matters arising from international sales contracts such as validity of contracts or property matters are not governed by the CISG. For this reason, the parties should choose the national law which would govern the matters that are not regulated in the CISG. On the other hand, the parties have the autonomy to determine the provisions of a contract by deviating from or modifying the provisions of the CISG, which can be named as freedom of contract in the context of the CISG. In general, there are no limits on party autonomy under the CISG as a principle. The only limit to party autonomy under the CISG is Art. 12 of the CISG which grants Contracting States the right to require that contracts or modifications to contract be made in writing.
CİSG'de Sözleşme Özgürlüğü, İrade Muhtariyeti ve Sınırları
Keywords: Hukuk